Cooperative Recruitment of FtsW to the Division Site of Bacillus subtilis - Gamba, Pamela; Hamoen, Leendert W.; Daniel, Richard A. (Frontiers in Microbiology, 2016)
Five essential proteins are known to assemble at the division site of Bacillus subtilis. However, the recruitment of the FtsW homolog is still unclear. Here, by taking advantage of GFP fusions and spore germination, we show that the assembly of FtsW is interdependent with the localization of PBP 2B and FtsL. Interestingly, the Z-ring appeared to disassemble upon prolonged depletion of late division proteins. Nevertheless, we could restore Z-ring formation and constriction by re-inducing FtsW, which suggests that the stability of the Z-ring is stimulated by the assembly of a functional division complex.